If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + 3) + -2(4x + -3) = 0 Reorder the terms: 3(3 + 2x) + -2(4x + -3) = 0 (3 * 3 + 2x * 3) + -2(4x + -3) = 0 (9 + 6x) + -2(4x + -3) = 0 Reorder the terms: 9 + 6x + -2(-3 + 4x) = 0 9 + 6x + (-3 * -2 + 4x * -2) = 0 9 + 6x + (6 + -8x) = 0 Reorder the terms: 9 + 6 + 6x + -8x = 0 Combine like terms: 9 + 6 = 15 15 + 6x + -8x = 0 Combine like terms: 6x + -8x = -2x 15 + -2x = 0 Solving 15 + -2x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + -2x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 0 + -15 -2x = 0 + -15 Combine like terms: 0 + -15 = -15 -2x = -15 Divide each side by '-2'. x = 7.5 Simplifying x = 7.5
| x-15.5=14.85-x | | x^2-49x+380=0 | | x+15.5=x+14.85 | | -3x-5+1+10=8+7x+8 | | 102(t+1)=102 | | 8m-3=11 | | 10h=5 | | 4m+11=7m-4 | | -4x-x=14-5x+2x | | 4s+-2s=-12 | | x^3+6x+7=0 | | 8y-3(5y-10)=2+7y-24 | | X^2-12x-5y^2+31=0 | | 2.04=(1.24-x)+(2.04-3X)+2x | | 5+4(5x-6)=9-5(2x+1) | | log(x+7)=1 | | 32x+21y=7200 | | 450=600-500r | | f(x)=100x^2-100x-600 | | 7x-9=73 | | a+(-3)=2a+5 | | 151x+(1-x)(425)=255 | | 36=x-24 | | 8-3n=-8 | | Y-7=5(x+2) | | 4z^2-18=-z | | 2x+51=4x-5 | | 2v^2+8=104 | | 2(5-d)=2-4 | | 0.05x=0.056 | | 3(2x-1)=5(x+4) | | -14m-20m-4m-12m-19=15 |